Modelo de diagnóstico para a geração de biogás em aterros sanitários - Ruoso, Ana Cristina (2021)
Demographic growth, urbanization, and industrialization are the main factors for the increase in the production of solid waste. Parallel to this scenario, countries current challenge is to meet the growing energy demand, reducing emissions of greenhouse gases and abdicating the use of non-renewable resources. Thus, energy recovery systems from biogas in landfills represent a solution. However, the Brazilian landfill gas recovery scenario is inefficient due to the uncertainty of the generation rate, considering that the impact of the factors that influence this process is linked to empirical relationships. Therefore, the decision on biogas recovery is a difficult task that must be made based on objective and measurable factors. Given this context, the goal of this study is to build a model to measure the impact of the various internal factors of landfills on biogas production in Brazil with focus on improving methane generation. The modeling of the factors in a structure that calculates each factor's impact in the biogas generation and its interrelation was conducted by Multiple-criteria decision analysis (MCDA), using the Analytic Hierarchy Process (AHP) method. The hierarchical structure was used to build the strategic map of the cause-and-effect relationship between operational factors and biodegradation factors in methane generation. Complementing the diagnostic modeling, the performance measurement regarding the biogas generation system was checked with a Performance Measurement System (SMD) based on Key Performance Indicators (KPI). The obtaining of the necessary values for the diagnosis modeling occurred through the application of three surveys, which correspond to the validation of the factors, weighting of the factors and evaluation of the companies' performance. The results showed that the operational factor that most impacts the methane generation system is the coating system followed by the gas drainage system and liquid management. While the biodegradation factors (system quantities) that most impact the process are the moisture content and the fraction of organic carbon. Regarding the performance measurement results, one of the companies presented a fully satisfactory performance, while the other companies achieved potentially satisfactory performance in relation to the level of achievement of the operational factors. The least contemplation occurred for the factor improvement of microbial activity. Finally, a computational self-diagnosis tool was developed to assist companies measure performance in biogas generation and system improvement.